Effect of crimson clover on the critical period of weed control in conservation tillage corn - Kumari, Annu; Price, Andrew J.; Korres, Nicholas E.; Gamble, Audrey; Li, Steve (Frontiers in Agronomy, 2023)
An increasing number of herbicide-resistant weeds, in addition to troublesome weeds, pose a significant challenge for chemical weed control in corn. Simultaneously, high-biomass cover crop adoption has gained popularity among farmers as an efficient weed control strategy. While the critical period of weed control (CPWC) following conventional tillage has been well documented, there is little knowledge of CPWC following high residue cover crops in corn. A two-year field experiment was conducted to estimate the influence of a high biomass crimson clover cover crop and conservation tillage on the critical period of weed control (CPWC) in corn. The experiment was implemented in a split-plot design in which the main plots were conventional tillage (CVT), conservation tillage following winter fallow (CT + WF), and conservation tillage following crimson clover (CT + CC), and the subplot included multiple durations of weedy plots (estimation of critical timing of weed removal (CTWR), i.e., beginning of weed control) and weed-free plots (estimation of critical weed-free period (CWFP), i.e., end of weed control). The results described that the estimated duration of CPWC in three systems, included CT + CC, CT + WF and CVT equals 2.8 wk., 3.5 wk., and 4.9 wk. respectively in 2019. In 2020, the predicted value of CTWR under CT + CC equals 3.8 week after planting (WAP) and the predicted values of CWFP were 5.1 and 5.7 WAP under CT + WF and CVT systems, but the model did not predict some values due to greater than 95% relative yield during most of growing season. In conclusion, the presence of a crimson clover cover crop delayed the CTWR and caused the early beginning of CWFP and hence shortened CPWC in 2019. During most of the growing season, weed biomass production was less under CT + CC plots than CVT and CT + WF systems in both years.